Einsatz eines didaktisch gelenkten Chatrooms im Fremdsprachenunterricht - Engler, Lela-Rose (Linguistik Online, 2003)
The use of virtual chatrooms for foreign language learning processes has lead to new research questions in the area of language acquisition. Assuming the differences between tutored and untutored chats tutored chats do not only offer the opportunity of synchronous communication between native and non-native speakers but also support the development of language abilities as reading and writing in the target language. In distance learning they can substitute for missing oral conversational classes.The conditions which either do or do not support the use of chatrooms have to be taken into account for planning and evaluating distance foreign language classes.